Life begins Quran stories for little hearts - Khan, Saniyasnain (Goodword Books : India, 2002)
Life Begins is an uplifting narrative that explores the themes of new beginnings and personal growth, encouraging readers to embrace change and discover the beauty and potential that each new chapter of life can bring.